A Qualitative Exploration of Children and Young People’s Experiences of the Secondary Relationships and Sex Education Curriculum - Cave, Sophie Nicole (2023)
Over the past decade numerous concerns have been raised about the effectiveness, appropriateness and standard of secondary school-based Sex and Relationships Education (SRE) in England (Greening, 2017; Ofsted, 2013). In March 2017, then Education Secretary, Justine Greening, announced statutory Relationships and Sex Education (RSE) for all secondary school pupils (Greening, 2017). The curriculum became constitutional on 1st of September 2020 (DfE, 2019). In view of this curriculum change, it is important to acknowledge previous literature that has recognised the importance of listening and advocating for the voice of children and young people (CYP) to promote positive sexual knowledge (Aggleton et al., 2000; Strange et al., 2006). At the time of writing this thesis, the researcher was unaware of any qualitative studies in England which had explored CYP’s experiences of the RSE curriculum post reforms. As such, the researcher aimed to explore CYP’s (aged 11-16) experiences of school based RSE, with an additional focus on how CYP experience the teaching of consent, as part of the RSE curriculum.